2018
DOI: 10.1093/cz/zoy026
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional, and cladistic patterns of variation in climatic niche breadths in terrestrial elapid snakes

Abstract: We obtained geo-referenced occurrence and climatic data from individual localities for 59 species of terrestrial elapid snakes, used phylogenetic generalized least squares regression to investigate spatial and cladistic patterns of variation in climatic niche breadths, and compared patterns within and across regions and clades to see if they parallel or differ from each other. Specifically, we test (1) whether a species’ climatic niche breadth on a given niche axis relates to its position along that axis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
2
6
0
1
Order By: Relevance
“…This explains why T. septentrionalis and T. sexlineatus have a similar Tp level (~32°C for both species; Yang et al, 2008). Therefore, as has been reported for other squamate reptiles (Lin & Wiens, 2017;Lin, Zhu, et al, 2019;Lin, Chen, et al, 2019;Stroud et al, 2020), low winter temperature rather than high summer temperature plays a key role in limiting the distribution of the two species farther north. The lower limit of thermal tolerance (CTMin) generally decreases with the increase in latitude and/or altitude in lizards (Qu et al, 2011).…”
Section: Discussionsupporting
confidence: 63%
“…This explains why T. septentrionalis and T. sexlineatus have a similar Tp level (~32°C for both species; Yang et al, 2008). Therefore, as has been reported for other squamate reptiles (Lin & Wiens, 2017;Lin, Zhu, et al, 2019;Lin, Chen, et al, 2019;Stroud et al, 2020), low winter temperature rather than high summer temperature plays a key role in limiting the distribution of the two species farther north. The lower limit of thermal tolerance (CTMin) generally decreases with the increase in latitude and/or altitude in lizards (Qu et al, 2011).…”
Section: Discussionsupporting
confidence: 63%
“…They found that climatic niche width decreased with temperature, but increased with precipitation, yet there was no evidence for a trade-off between temperature and precipitation niche widths. Later studies on more taxonomically restricted datasets tended to confirm the relationships between niche position and width for temperature and precipitation, as well as the absence of a trade-off between climatic niche breadths between axes (i.e., lacertid lizards [Fang et al, 2019], varanid lizards [Lin & Wiens, 2017], elapid snakes [Lin et al, 2019]), but the validity of this pattern for more inclusive taxa is still poorly known. However, the fact that Liu et al (2020) found congruent evidence against this trade-off for vertebrates and plants suggests that it might indeed represent a general principle of climatic niche evolution.…”
Section: Introductionmentioning
confidence: 99%
“…To reveal these diversification processes, it is crucial to study niche equivalency and similarity during initial stages of diversification (Costion et al 2015). As in other animal taxa, climatic niche analysis is commonly used in reptiles to achieve this goal, because climatic variables play an important role in species distribution and diversification (Myers et al 2013;Fang et al 2019;Lin et al 2019).…”
Section: Introductionmentioning
confidence: 99%